Existential Anxiety in connection with Gothic Aesthetics in Forūgh Farrokhzād's Poetry - Ghodsieh Rezvanian (مطالعات زبانی و بلاغی)
Forūgh Farrokhzād is one of the few controversial poets in Persian literature whose depth of thought has not been thoroughly explored because of being a woman and presenting a critical and rebellious new face of a woman with "inky fingers". However, though the nature of this protest is social, it comes from a deeper origin, which is a philosophical one. Anxiety is the main treasure of her poetry, a component that none of Forūgh Farrokhzād's poems; whether the rebellious-emotional poems of the first phase or the critical-philosophical poems of the second phase are not devoid of. To use Kierkegaard’s idea, this feature is inherent in her poetry. Therefore, imagery and melodramatic narrative are reflected with a special aesthetic suitable for this motif, i.e. gothic aesthetics. This article, using an analytical descriptive method, examines how gothic aesthetics converges with existential anxiety and its manifestations, loneliness, doubt and suspense in the two metaphors of wind and night in her poetry and concludes that Farrokhzād lived the philosophy of existentialism in her poetry.